Evaluation of the COVID-19 pandemic using an algorithm based on the Bateman function: prediction of disease progression using observational data for the city of Heidelberg, Germany - Merle, Uta; Laßmann, Axel; Dressel, Alexander R.; Braun, Peter (International journal of clinical pharmacology and therapeutics, 2020)
The COVID-19 pandemic has been evaluated using an algorithm based on the Bateman function in a modified SIR/SIZ-Model. Prediction of the number of persons carrying the live COVID-19 coronavirus (I) in a susceptible population (S) was achieved using two rate constants describing the rate of increase and decrease in the number of infectious persons on a daily basis. The model was verified using observational data for the city of Heidelberg, Germany. Three hypothetical scenarios, having their counterparts in practice were considered, namely Scenario A - No restrictions on the population; Scenario B - Assumption of a 10-fold higher number of infections than observed; Scenario C - Protective measures introduced only for elderly persons. It could be demonstrated using the model that the lockdown measures introduced prevented a major medical emergency and possibly a near catastrophe in the region. It was further demonstrated that the prospective application of the model can facilitate realtime decisions on pandemic management strategy for the population. This is achieved by curve-fitting for the rate constants, determinants for the number of infectious persons. The calculated maximum numbers of infected and infectious persons daily increased in proportion to the number of persons initially susceptible to the infection. After appearance of the first two infections in Heidelberg, the calculated maximum number of persons carrying live virus was 2,291 at Day 102 (Scenario B), 18,936 infectious persons at Day 139 (Scenario C) and 22,535 infectious at Day 142 (Scenario A). In Scenario A, high values would have persisted for 6 months during which a total of 124,301 persons would have been infected in Heidelberg. The model predicted that the virus would have disappeared within 1 year after being first detected. A disease catastrophe of this magnitude would not be expected provided the rate constant (α) for the rate of increase in the number of infectious persons remained lower than the rate constant (β) for the fall in number of infectious persons.
Gesehen am 28.07.2020